2012
DOI: 10.1353/ajm.2012.0034
|View full text |Cite
|
Sign up to set email alerts
|

Plücker forms and the theta map

Abstract: Let SUX (r, 0) be the moduli space of semistable vector bundles of rank r and trivial determinant over a smooth, irreducible, complex projective curve X. The theta map θr : SUX (r, 0) → P N is the rational map defined by the ample generator of Pic SUX (r, 0). The main result of the paper is that θr is generically injective if g >> r and X is general. This partially answers the following conjecture proposed by Beauville: θr is generically injective if X is not hyperelliptic. The proof relies on the study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Brivio and Verra [BV12] showed that is generically injective for a general curve of genus , partially answering a conjecture of Beauville [Bea06, §6]. We apply the aforementioned construction to give the following sharpening of Brivio and Verra’s result.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Brivio and Verra [BV12] showed that is generically injective for a general curve of genus , partially answering a conjecture of Beauville [Bea06, §6]. We apply the aforementioned construction to give the following sharpening of Brivio and Verra’s result.…”
Section: Introductionmentioning
confidence: 73%
“…We apply this construction to give an improvement of a result of Brivio and Verra [BV12]. To describe this application, we need to recall some more objects.…”
Section: Introductionmentioning
confidence: 99%
“…There are also good descriptions of the image of θ for r = 2 g = 2, 3 [28] [34], r = 3, g = 2 [31] [29], r = 2, g = 4 [33]. Moreover, it has recently been shown in [12] that if C is general and g >> r then θ is generically injective.…”
Section: The Theta Mapmentioning
confidence: 99%
“…These spaces are interesting by themselves as higher dimensional varieties but also for important related constructions: just to mention some, one can consider higher-rank Brill-Noether theory, Theta divisors and Theta functions and the moduli spaces of coherent systems. For surveys on these topics see, for example [3,6,7]; for some results by the authors see [5,8,[11][12][13][14]. When the curve is singular, these spaces are not in general complete.…”
Section: Introductionmentioning
confidence: 99%